Palladium-copper bimetal-based nano-catalyst as well as preparation method and application thereof
The palladium-copper bimetallic nanocatalyst prepared by step-by-step reduction method solves the problems of low carbon dioxide conversion and insufficient selectivity of low carbon alcohol in existing catalysts, and achieves efficient carbon dioxide conversion and low carbon alcohol selectivity, and the catalyst stability and preparation process have also been improved.
Patent Information
- Application Number
- CN202411822041.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing catalysts for hydrogenation of carbon dioxide to prepare low-carbon alcohols have problems such as low carbon dioxide conversion, low-carbon alcohol selectivity, poor catalyst stability, and complex preparation process.
A palladium-copper bimetallic nanocatalyst is provided, prepared by step-by-step reduction method, palladium nanoparticles are deposited on the oxide support, and copper nanoparticles are deposited on the surface of palladium nanoparticles, and the ratio of palladium and copper and the type of oxide support are regulated to improve catalytic activity and stability.
It improves the conversion rate of carbon dioxide and the selectivity of low-carbon alcohols, has high catalyst activity and good stability, and is simple in preparation and easy to operate.
Smart Images

Figure CN119608183A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal-based catalysts, and specifically relates to a palladium-copper bimetallic-based nanocatalyst and a preparation method and application thereof, and in particular relates to the application of the palladium-copper bimetallic-based nanocatalyst in the preparation of low-carbon alcohols by hydrogenation of carbon dioxide. Background Art
[0002] In recent years, the concentration of carbon dioxide in the atmosphere has increased significantly, posing a huge threat to the living environment of all mankind. The reduction and utilization of carbon dioxide has become an important global issue. As a cheap and renewable carbon and oxygen resource, converting carbon dioxide into high-value-added chemicals can not only reduce the pressure of carbon dioxide emissions, but also realize the recycling of carbon resources. It is a fundamental way to achieve green chemistry and solve energy and environmental problems.
[0003] At present, the research on converting carbon dioxide into high value-added chemicals is mainly focused on the production of methanol by hydrogenation of carbon dioxide, while low-carbon alcohols have higher energy density and higher market prices than methanol. Taking ethanol as an example, the current average market price of ethanol is 6,500 yuan / ton, and the calorific value is 6,350 kcal / kg, while the average market price of methanol is 2,200 yuan / ton, and the calorific value is 4,650 kcal / kg. Therefore, the preparation of low-carbon alcohols (methanol, ethanol, propanol) by hydrogenation of carbon dioxide further broadens the scope of carbon dioxide utilization, and has both economic and social benefits.
[0004] The key technology for the hydrogenation of carbon dioxide to synthesize low-carbon alcohols lies in the design and development of catalysts. Currently reported catalysts mainly include precious metal-based (palladium, rhodium, platinum, etc.), copper-based, molybdenum-based and cobalt-based catalysts. Patent CN116899598A discloses a PdFe / Fe 3 O 4 Catalyst. The catalyst uses an iron salt solution as a precursor, prepares iron oxide by a sol-gel method or a precipitation method, and then loads precious metal palladium and is prepared by high-temperature reduction. It is suitable for the reaction of hydrogenating carbon dioxide to synthesize low-carbon alcohols. However, the reaction products are mainly alkanes and carbon monoxide. Patent CN103191747B discloses a CuZn / ZrO 2Preparation method of catalyst. The catalyst uses copper nitrate, zinc nitrate and zirconium nitrate as precursors and sodium carbonate as a precipitant, and is prepared by a coprecipitation method, which is suitable for the reaction of hydrogenating carbon dioxide to synthesize low-carbon alcohols. However, the preparation process of the catalyst is complicated and cumbersome, and the preparation takes more than 50 hours. Patent CN201510369970 discloses a rhodium-based catalyst. In the presence of a ruthenium complex, a rhodium complex catalyst, an iodide and a solvent, the catalyst hydrogenates carbon dioxide and hydrogen in a reactor to obtain ethanol and high-carbon alcohols. However, the catalyst is a homogeneous catalyst and is only suitable for autoclave reactions. In addition, the catalyst requires expensive organic ligands during the synthesis process, and the air sensitivity of the organic ligands makes the catalyst less stable. Bai et al. reported the preparation of a palladium-copper-based catalyst by a one-step reduction method, and showed selectivity for ethanol in the hydrogenation reaction of carbon dioxide, but the catalyst is only suitable for autoclave reactions and has poor industrial prospects (J.Am.Chem.Soc.2017,139,6827-6830).
[0005] In summary, the catalysts for preparing low-carbon alcohols by hydrogenating carbon dioxide in the prior art still have disadvantages such as low carbon dioxide conversion rate, low product alcohol selectivity, poor catalyst stability, and complex preparation process. Summary of the invention
[0006] The present invention provides a palladium-copper bimetallic nanocatalyst and its preparation method and application to solve the problems of low carbon dioxide conversion rate and low selectivity of low carbon alcohols in the existing technology of converting carbon dioxide into high value-added low carbon alcohols. The preparation method has a simple operation process, and the prepared catalyst has good activity and stability. The catalyst is applied in the reaction of preparing low carbon alcohols by hydrogenation of carbon dioxide, and the conversion rate of carbon dioxide is high and the selectivity of low carbon alcohols is high.
[0007] To achieve the above object, the technical solution of the present invention is as follows:
[0008] The invention provides a palladium-copper bimetallic nanocatalyst, comprising an oxide carrier, palladium nanoparticles deposited on the surface of the oxide carrier, and copper nanoparticles deposited on the surface of the palladium nanoparticles, wherein the molar ratio of the palladium element to the copper element is 0.1-10, and the loading amount of the palladium element relative to the oxide carrier is 1wt.%-5wt.%.
[0009] Preferably, the size of the palladium-copper bimetallic-based nanocatalyst is 6 nm to 20 nm.
[0010] Preferably, the oxide is one or more of silicon dioxide, aluminum oxide, titanium dioxide, zirconium oxide, and cerium oxide.
[0011] The present invention also provides a method for preparing the above-mentioned palladium-copper bimetallic-based nanocatalyst, the steps of which are as follows:
[0012] (1) dissolving a palladium precursor and an oxide support in a solvent I, which is referred to as solution a; dissolving a reducing agent I in deionized water, which is referred to as solution b;
[0013] The reducing agent I is one or more of sodium borohydride, potassium borohydride, and hydrazine hydrate, the molar ratio of the reducing agent I to the palladium element is 10:1 to 2:1, and the amount of the oxide carrier is 1 wt.% to 5 wt.% based on the loading amount of the palladium element relative to the oxide carrier;
[0014] (2) Add solution b dropwise into solution a and stir for several hours to form a precipitate;
[0015] (3) After centrifugation and washing, the obtained precipitate is redispersed in solvent II and recorded as solution c;
[0016] (4) dissolving a copper precursor in deionized water, referred to as solution d; mixing solution d and solution c evenly to obtain a mixed solution; in the mixed solution, the molar ratio of copper element to palladium element is 1:10 to 1:2;
[0017] (5) Dissolve the reducing agent II in deionized water, referred to as solution e; add solution e dropwise into the mixed solution and stir for several hours to form a precipitate;
[0018] The reducing agent II is one or more of ascorbic acid, ammonia borane complex, diborane, and ethylene glycol, and the molar ratio of the reducing agent II to copper is 10:1 to 2:1;
[0019] (6) The obtained precipitate is centrifuged, washed, dried, and ground into powder to obtain a palladium-copper bimetallic-based nanocatalyst.
[0020] Preferably, in step (1), the palladium precursor is one or more of palladium acetate, palladium chloride, palladium nitrate, palladium acetylacetonate, and potassium tetrachloropalladate.
[0021] Preferably, in step (1), the solvent I is one or more of deionized water, acetone, methanol, ethanol, and ethylene glycol, and the concentration of palladium in solution a is 0.05 mol / L to 1 mol / L.
[0022] Preferably, in step (2), the stirring speed is 400 r / min to 1000 r / min, and the stirring time is 1 to 5 h.
[0023] Preferably, in step (3), the centrifugal washing is performed by centrifugation washing with deionized water and anhydrous ethanol for 1 to 3 times respectively.
[0024] Preferably, in step (3), the solvent II is one or more of deionized water, acetone, methanol, ethanol, and ethylene glycol.
[0025] Preferably, in step (4), the copper precursor is one or more of copper nitrate, copper chloride, copper sulfate, copper acetylacetonate, and copper acetate.
[0026] Preferably, in step (5), the stirring speed is 400 r / min to 1000 r / min, and the stirring time is 1 h to 5 h;
[0027] Preferably, in step (6), the washing method is: centrifugal washing with deionized water and anhydrous ethanol for 1 to 5 times respectively.
[0028] Preferably, in step (6), the drying temperature is 60° C. to 150° C., and the drying time is 5 h to 24 h.
[0029] The present invention also provides application of the palladium-copper bimetallic nanocatalyst in synthesizing low-carbon alcohols by hydrogenating carbon dioxide.
[0030] Preferably, the low-carbon alcohol is one or more of methanol, ethanol and propanol.
[0031] Preferably, the steps are as follows:
[0032] (1) performing hydrogen pre-reduction treatment on the palladium-copper bimetallic nanocatalyst, wherein the pre-reduction treatment conditions are: space velocity of 3000 mL / g / h to 10000 mL / g / h, temperature of 200° C. to 400° C., and reduction time of 0.5 h to 5 h;
[0033] (2) tableting, crushing, and sieving the pre-reduced palladium-copper bimetallic nanocatalyst to a particle size of 10 to 80 meshes, and then loading it into a fixed bed reactor to carry out a carbon dioxide hydrogenation reaction to obtain a low-carbon alcohol;
[0034] The reaction conditions are as follows: reaction temperature 200°C to 400°C, reaction pressure 2MPa to 4MPa, space velocity 3000mL / g / h to 8000mL / g / h, and the gas used is CO at a volume ratio of 1:1 to 1:5. 2 and H 2 of mixed gas.
[0035] The principle of the present invention is:
[0036] The palladium-copper bimetallic nanocatalyst of the present invention is prepared by a step-by-step reduction method. The types and concentrations of the reducing agents used in the two reductions are different. The palladium precursor is reduced to palladium nanoparticles by reducing agent I and deposited on an oxide carrier. Then, the copper precursor is deposited on the surface of the palladium nanoparticles by reducing agent II, and finally the palladium-copper bimetallic nanocatalyst is obtained.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The preparation method of the palladium-copper bimetallic-based nanocatalyst of the present invention has a simple process, is easy to operate, and has wide applicability.
[0039] (2) The palladium-copper bimetallic nanocatalyst of the present invention has high activity, good stability, and high atomic utilization rate. Different distributions of alcohol products can be obtained by adjusting the ratio of palladium and copper and changing the type of oxide carrier.
[0040] (3) The present invention precisely regulates the reduction rate of metal ions by regulating the concentration and type of the reducing agent, so that palladium and copper in the catalyst exist in the form of highly dispersed bimetallic. This can not only strengthen the interaction between the synergistic palladium and copper metals, but also improve the metal-support interaction between the bimetallic component and the support, which is beneficial to the activation of carbon dioxide and the regulation of reaction intermediates, thereby improving the conversion rate of carbon dioxide and the selectivity of low-carbon alcohols, which is much higher than that of a single palladium-based catalyst, a copper-based catalyst, and a palladium-copper catalyst prepared by a direct one-step reduction method. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 This is a high-resolution transmission electron microscopy (HR-TEM) photograph of the palladium-copper bimetallic-based nanocatalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0043] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below in conjunction with embodiments.
[0044] In the following examples, various processes and methods not described in detail are conventional methods known in the art. Unless otherwise specified, the materials, reagents, devices, instruments, equipment, etc. used in the following examples can be obtained from commercial sources.
[0045] Example 1
[0046] First, 2g of silica and 0.086g of palladium nitrate were dissolved in 6mL of deionized water and stirred evenly to obtain a mixed solution. An excess of sodium borohydride aqueous solution was added dropwise to the mixed solution and stirred for 1h (stirring speed was 400r / min~1000r / min) to form a precipitate, wherein the molar ratio of sodium borohydride to palladium nitrate was 10:1. The obtained precipitate was centrifuged and washed twice with deionized water and anhydrous ethanol respectively, redispersed in deionized water, and copper nitrate aqueous solution was added and stirred evenly to obtain a mixed solution, wherein the molar ratio of copper nitrate to palladium nitrate was 1:3. An ammonia borane complex aqueous solution was added dropwise to the mixed solution and stirred for 2h (stirring speed was 400r / min~1000r / min) to form a precipitate, wherein the molar ratio of ammonia borane complex to copper nitrate was 5:1. The obtained precipitate was centrifuged and washed 3 times with deionized water and anhydrous ethanol respectively, and then dried at 60°C for 12h to obtain a palladium-copper bimetallic nanocatalyst.
[0047] The morphology and composition of the Pd-Cu bimetallic nanocatalyst were observed using transmission electron microscopy (TEM) or high-resolution transmission electron microscopy (HRTEM). Figure 1 As shown, it was observed that palladium and copper in the palladium-copper bimetallic-based nanocatalyst obtained in Example 1 existed in the form of bimetallic, and the size of the palladium-copper bimetallic-based nanocatalyst was about 8 nm.
[0048] Example 2
[0049] The molar ratio of copper nitrate to palladium nitrate in Example 1 was replaced with 1:8, and the other operations were the same as in Example 1.
[0050] Example 3
[0051] The molar ratio of copper nitrate to palladium nitrate in Example 1 was replaced with 1:10, and other operations were the same as in Example 1.
[0052] Example 4
[0053] The molar ratio of copper nitrate to palladium nitrate in Example 1 was replaced with 1:1, and the other operations were the same as in Example 1.
[0054] Example 5
[0055] The palladium precursor in Example 1 was replaced with palladium acetylacetonate, and the other operations were the same as in Example 1.
[0056] Example 6
[0057] The copper precursor in Example 1 was replaced with copper acetate, and other operations were the same as in Example 1.
[0058] Example 7
[0059] The molar ratio of the ammonia borane complex to copper nitrate in Example 1 was changed to 10:1, and the other operations were the same as in Example 1.
[0060] Example 8
[0061] The oxide carrier silicon dioxide in Example 1 was replaced by aluminum oxide. Other operations were the same as in Example 1.
[0062] Example 9
[0063] The oxide carrier silicon dioxide in Example 1 was replaced by titanium dioxide. Other operations were the same as in Example 1.
[0064] Example 10
[0065] Dissolve 2g of silica and 0.086g of palladium nitrate in 6mL of deionized water and stir evenly. Add an excess of sodium borohydride aqueous solution drop by drop to the mixed solution and stir for 1h (stirring speed is 400r / min~1000r / min) to form a precipitate, wherein the molar ratio of sodium borohydride to palladium nitrate is 5:1. Wash the obtained precipitate with deionized water and anhydrous ethanol by centrifugation twice, redisperse it in deionized water, add copper nitrate aqueous solution and stir evenly to obtain a mixed solution, wherein the molar ratio of copper nitrate to palladium nitrate is 1:3. Add ascorbic acid aqueous solution drop by drop to the mixed solution and stir for 2h (stirring speed is 400r / min~1000r / min) to form a precipitate, wherein the molar ratio of ascorbic acid to copper nitrate is 2:1. Wash the obtained precipitate with deionized water and anhydrous ethanol by centrifugation 3 times, and dry it at 60℃ for 12h to obtain a palladium-copper bimetallic nanocatalyst.
[0066] Comparative Example 1
[0067] Dissolve 2g of silicon dioxide and 0.086g of palladium nitrate in 6mL of deionized water and stir evenly to obtain a mixed solution. Add excess sodium borohydride aqueous solution dropwise to the mixed solution and stir for 1h (stirring speed is 400r / min~1000r / min) to form a precipitate, in which the molar ratio of sodium borohydride to palladium nitrate is 10:1. Wash the obtained precipitate with deionized water and anhydrous ethanol by centrifugation twice, and dry it at 60°C for 12h to obtain a catalyst.
[0068] Comparative Example 2
[0069] Dissolve 2g of silicon dioxide and 0.12g of copper nitrate in 6mL of deionized water and stir evenly to obtain a mixed solution. Add excess sodium borohydride aqueous solution dropwise to the mixed solution and stir for 1h (stirring speed is 400r / min~1000r / min) to form a precipitate, in which the molar ratio of sodium borohydride to copper nitrate is 10:1. Wash the obtained precipitate with deionized water and anhydrous ethanol by centrifugation twice, and dry it at 60℃ for 12h to obtain a catalyst.
[0070] Comparative Example 3
[0071] Dissolve 2g of silicon dioxide, 0.086g of palladium nitrate, and 0.12g of copper nitrate in 6mL of deionized water and stir evenly to obtain a mixed solution. Add excess sodium borohydride aqueous solution dropwise to the mixed solution and stir for 1h (stirring speed is 400r / min~1000r / min) to form a precipitate, in which the molar ratio of sodium borohydride to copper nitrate and palladium nitrate is 10:1. Wash the obtained precipitate with deionized water and anhydrous ethanol by centrifugation twice, and dry it at 60°C for 12h to obtain a catalyst.
[0072] Comparative Example 4
[0073] The reduction sequence in Example 1 was changed to first adding a copper precursor, reducing it using an ammonia borane complex, and then adding a palladium precursor and reducing it using sodium borohydride. Other operations were the same as in Example 1.
[0074] Comparative Example 5
[0075] The ammonia borane complex in Example 1 was replaced by sodium borohydride, and other operations were the same as in Example 1.
[0076] The reaction performance of the catalysts prepared in Examples 1-10 and Comparative Examples 1-5 was evaluated.
[0077] Before the reaction test, the catalyst was pre-reduced with hydrogen. The pre-reduction conditions were: air velocity of 8000 mL / g / h, pretreatment conditions of 300°C, and reduction for 2 hours. After the temperature dropped to room temperature, the pre-reduced catalyst was tableted, crushed, and sieved to a particle size of 10 to 80 meshes, and then loaded into a fixed bed reactor for reaction performance evaluation. The reaction temperature was 270°C, the reaction pressure was 3 MPa, the air velocity was 6000 mL / g / h, and the gas used was CO with a volume ratio of 1:1 to 1:5. 2 and H 2 of mixed gas.
[0078] The reaction test results are shown in Table 1.
[0079] Table 1 Catalyst activity evaluation results
[0080]
[0081]
[0082] As can be seen from Table 1, when the catalyst prepared by one-step direct reduction or a single palladium-based catalyst and a copper-based catalyst, the conversion rate of carbon dioxide and the selectivity of alcohols are all low. In addition, changing the reduction order also has a greater impact on catalytic performance. The catalyst of the present invention shows good catalytic performance in the catalytic carbon dioxide hydrogenation reaction to prepare low-carbon alcohols, and the catalytic activity and the selectivity of low-carbon alcohols have been significantly improved. By changing the molar ratio of palladium copper, the type of carrier and the type and concentration of the reducing agent at the same time, the product distribution of low-carbon alcohols can be effectively regulated.
[0083] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the embodiments. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. The obvious changes or modifications derived from them are still within the protection scope of the invention.
Claims
1. A palladium-copper bimetallic nanocatalyst, characterized in that: The invention comprises an oxide carrier, palladium nanoparticles deposited on the surface of the oxide carrier, and copper nanoparticles deposited on the surface of the palladium nanoparticles. The molar ratio of palladium element to copper element is 0.1-10, and the loading amount of palladium element relative to the oxide carrier is 1wt.%-5wt.%.
2. The palladium-copper bimetallic nanocatalyst according to claim 1, characterized in that: The size of the palladium-copper bimetallic-based nanocatalyst is 6nm-20nm.
3. The palladium-copper bimetallic nanocatalyst according to claim 1, characterized in that: The oxide is one or more of silicon dioxide, aluminum oxide, titanium dioxide, zirconium oxide, and cerium oxide.
4. The method for preparing a palladium-copper bimetallic nanocatalyst according to any one of claims 1 to 3, characterized in that: Here are the steps: (1) dissolving a palladium precursor and an oxide support in a solvent I, which is referred to as solution a; dissolving a reducing agent I in deionized water, which is referred to as solution b; The reducing agent I is one or more of sodium borohydride, potassium borohydride, and hydrazine hydrate, the molar ratio of the reducing agent I to the palladium element is 10:1 to 2:1, and the amount of the oxide carrier is 1 wt.% to 5 wt.% based on the loading amount of the palladium element relative to the oxide carrier; (2) Add solution b dropwise into solution a and stir for several hours to form a precipitate; (3) After centrifugation and washing, the obtained precipitate is redispersed in solvent II and recorded as solution c; (4) dissolving a copper precursor in deionized water, referred to as solution d; mixing solution d and solution c evenly to obtain a mixed solution; in the mixed solution, a molar ratio of palladium element to copper element is 0.1 to 10; (5) Dissolve the reducing agent II in deionized water, referred to as solution e; add solution e dropwise into the mixed solution and stir for several hours to form a precipitate; The reducing agent II is one or more of ascorbic acid, ammonia borane complex, diborane, and ethylene glycol, and the molar ratio of the reducing agent II to the copper element is 10:1 to 2:1; (6) The obtained precipitate is centrifuged, washed, dried, and ground into powder to obtain a palladium-copper bimetallic-based nanocatalyst.
5. The preparation method of palladium-copper bimetallic nanocatalyst according to claim 4, characterized in that: In step (1), the palladium precursor is one or more of palladium acetate, palladium chloride, palladium nitrate, palladium acetylacetonate, and potassium tetrachloropalladate; The solvent I is one or more of deionized water, acetone, methanol, ethanol, and ethylene glycol. In the solution a, the concentration of the palladium element is 0.05 mol / L to 1 mol / L.
6. The method for preparing a palladium-copper bimetallic nanocatalyst according to claim 4, wherein: In step (2), the stirring speed is 400 r / min to 1000 r / min, and the stirring time is 1 h to 5 h; And / or, in step (5), the stirring speed is 400 r / min to 1000 r / min, and the stirring time is 1 h to 5 h.
7. The method for preparing a palladium-copper bimetallic nanocatalyst according to claim 4, wherein: In step (3), the solvent II is one or more of deionized water, acetone, methanol, ethanol, and ethylene glycol; And / or, in step (4), the copper precursor is one or more of copper nitrate, copper chloride, copper sulfate, copper acetylacetonate, and copper acetate.
8. The method for preparing a palladium-copper bimetallic nanocatalyst according to claim 4, wherein: In step (3), the centrifugal washing method is: using deionized water and anhydrous ethanol for centrifugal washing 1 to 3 times respectively; And / or, in step (6), the washing method is: centrifugal washing with deionized water and anhydrous ethanol for 1 to 5 times respectively; the drying temperature is 60° C. to 150° C., and the drying time is 5 h to 24 h.
9. Use of the palladium-copper bimetallic nanocatalyst according to any one of claims 1 to 3 in the synthesis of low-carbon alcohols by hydrogenation of carbon dioxide.
10. The use of the palladium-copper bimetallic nanocatalyst according to claim 9 in the synthesis of low-carbon alcohols by hydrogenation of carbon dioxide, characterized in that: (1) performing hydrogen pre-reduction treatment on the palladium-copper bimetallic nanocatalyst, wherein the pre-reduction treatment conditions are: space velocity of 3000 mL / g / h to 10000 mL / g / h, temperature of 200° C. to 400° C., and reduction time of 0.5 h to 5 h; (2) tableting, crushing, and sieving the pre-reduced palladium-copper bimetallic nanocatalyst to a particle size of 10 to 80 meshes, and then loading it into a fixed bed reactor to carry out a carbon dioxide hydrogenation reaction to obtain a low-carbon alcohol; The reaction conditions are: reaction temperature 200°C to 400°C, reaction pressure 2MPa to 4MPa, space velocity 3000mL / g / h to 8000mL / g / h, and the gas used is a mixture of CO2 and H2 in a volume ratio of 1:1 to 1:5; The low-carbon alcohol is one or more of methanol, ethanol and propanol.
Citation Information
Patent Citations
A method for synthesizing lower alcohols by hydrogenation of carbon dioxide using a catalyst
CN103191747B
Method for synthesis of ethanol and higher alcohol by carbon dioxide hydrogenation
CN105001048A
Catalyst for catalyzing hydrogenation of carbon dioxide to synthesize low-carbon alcohol as well as preparation method and application of catalyst
CN116899598A
Catalyst for synthesizing methanol through hydrogenation of carbon dioxide and preparation method of catalyst
CN109999833A
Alkyne selective hydrogenation catalyst as well as preparation method and application thereof
CN115990477A